Voltammetric and spectroscopic studies of water/formamide ratios in the production of the cerium (III) hexacyanoferrate (II) nanoparticles - do Carmo, Devaney Ribeiro [UNESP]; de Oliveira, Denys Ribeiro [UNESP] (Wiley, 2023)
The present study describes the simple and fast preparation of Cerium (III) hexacyanoferrate (II) (CeHCF) solid nanoparticles at three different water/formamide (%) ratios used as solvent (v/v) (100:0, 80:20, 0:100). CeHCF nanoparticles (Nps) were characterized by fourier transform infrared pectroscopy (FTIR), x-ray diffraction (XRD), scanning electron microscopy (SEM), zeta potential and cyclic voltammetry (CV). Electrodes modified with CeHCF presented a well-defined redox pair with formal potential (Eo′) of approximately 0.29 V (vs. Ag/AgCl(sat) attributed to the Fe2 +/Fe3+ redox pair in the presence of cerium (III)). The Nps in the three systems investigates, presents a random size distribution to different surface, where most were distributed between 20 and 160 nm. Considering the three investigated systems, only CeHCF-1 (100:0) was sensitive to L-dopamine, presenting a linear signal region as a function of L-dopamine concentrations, with a limit of detection (LD) of 0.125 mmol L−1, limit of quantification (LQ) of 0.419 mmol L−1 and amperometric sensitivity (S) of 148.16 μA mmol L−1.
Keywords: cerium (III) hexacyanoferrate (II); electrochemical sense; L-dopamine; metal nanoparticles; voltammetry